Experiences of Vulnerable Children in a South African Public Child and Youth Care Centre - van der Merwe, Petro (International Journal of Criminology and Sociology, 2022)
The article reflects on community engagement as an excellent method to build upon researchers’ cumulative knowledge in a specific discipline and to demonstrate the integration of that knowledge with real-life issues. This is followed by a literature review that examines complex life situations of the interaction between parenting and child abuse, specifically between structures and child welfare systems, that capture the lines between circumstances and individual action. A phenomenological approach is adopted of descriptive qualitative nature regarding the perception of the psychosocial well-being of vulnerable children in a child and youth care centre in Tshwane, South Africa. Findings point to the nature and extent of violence against children in South Africa. As this article does not cover the complete field of the welfare system, the aim is to foster a greater understanding of this system, which might lead to better and more research on vulnerable children after being placed in a child and youth care centre. Explanations offered include legislation and coordination mechanisms, including the associated gaps and challenges.